Imagination warfare: targeting youths on the everyday battlefields of the 21st century. (3rd May 2016) - Giroux, Henry A.; Evans, Brad
ABSTRACT: Working on from the understanding that youths have become a notable, if under-theorized object for power and violence in the everyday battlefields of the twenty-first century, this paper offers a rethinking of the politics of violence in the contemporary period. Moving beyond conventional understandings of the violence that neatly map it out in terms of civilization versus barbarity, it is our contention that both sides to the conflict have effectively created a Gordian knot through which the recourse to violence reigns supreme. Indeed, once we recognize that the conflicts of today are fought over the site of imagination itself, so there is a need to offer a fundamental rethink if we are to break the cycle of violence, and ensure that our collective futures are not violently fated.